Community stakeholders’ views on reducing violence against women in Pakistan - Ali, Tazeen Saeed (BMC Womens Health, 2020)
BACKGROUND: Nearly half of the women experience violence across their lifespan in all the provinces of Pakistan at an alarming rate. Despite knowing the prevalence, there has been meager progress in developing strategies to combat violence at individual, family, or community level. Many interventions suggested in other countries have been pilot tested but the effects of those interventions had been limited. Therefore, the aim of this study is to understand the voices of stakeholders to reduce Violence Against Women (VAW) and to explore the possible community-based strategies that could be implemented in Pakistan. METHODS: A total of 14 Key Informant Interviews (KIIs) and 18 Focus Group Discussions (FGDs) were held across all four provinces of Pakistan. Participants were purposefully recruited and all the interviews were audio-recorded. Transcriptions were open coded and content analysis was done to emerge codes, categories and themes. Ethical approval was obtained from Aga Khan University Ethics Review Committee. RESULTS: Three major themes emerged on community members and stakeholders’ views on VAW: a) community’s perception of VAW b) the repercussions of VAW, and c) multiple voices regarding strategies to reduce VAW. Participants voiced the need of standing against the status quo, role of awareness and education: regarding capacity building skills, promotion of women rights and women empowerment through Life Skills Based Education (LSBE) through national health works program, has been proposed as an innovative strategy to reduce VAW. CONCLUSIONS: The responsibility to bring about a substantial change in behavior and attitudes must begin with engaging men in all the interventions that aim to reduce violence. Since, VAW is very much linked with the cultural norms, so, without community stakeholder’s involvement and participation it could never be reduced. Keeping the existing socio-cultural dynamics in mind, the need of time is to design and implement innovative interventions that are culturally and contextually appropriate and can be expanded across the country.